Okara: a promising resource for novel bioflocculant synthesis - Agustin, Yuana Elly; He, Ning; Yeap, Swee Keong; Luthfi, Abdullah Amru Indera; Ding, Gongtao; Abdul, Peer Mohamed; Abdul Manaf, Shareena Fairuz; Jamali, Nur Syakina; Chen, Binghui; Tan, Jian Ping (Italian Association of Chemical Engineering - AIDIC, 2024)
The Sustainable Development Goal no 12 (SDG 12) focuses on responsible consumption and production, which includes reducing waste generation, achieving environmentally chemical management, and encouraging companies to adopt sustainable practices. Okara, an insoluble residue from soybean processing, has been identified as a potential carbon and nitrogen resource for bioflocculants synthesis. This resource can reduce production costs which can make microbial bioflocculants more competitive, and reduce the amount of organic waste that ends up in landfills, where it contributes to the release of methane – a potent greenhouse gas. Bioflocculants can improve water quality by removing pollutants and contaminants from industrial wastewater. However, the low efficiency of bioconversion of okara to bioflocculants remains a major issue. This study focuses on investigating the potential of novel bioflocculant production of Bacillus licheniformis CGMCC 2876 using okara as an alternative carbon source and to optimize conditions for its use. The result showed that the use of okara as an alternative substrate resulted in 89.2 % flocculation activity of the kaolin suspension when Ca2+ was used as a coagulant and pH was 12. By utilizing okara as a carbon source in novel bioflocculant synthesis, enhances waste management efficiency and reduces environmental impact, contributing to sustainable infrastructure development and cleaner manufacturing technologies that reduce pollution and industrial operations’ carbon footprint.